The Influence of Brand Awareness, Brand Image, and Word of Mouth on Brand Loyalty Through Brand Trust as an Intervening Variable in Vaseline Body Lotion Consumers in Mojokerto City - Rahmatin, Devina Zulia; Rusdianto, R. Yuniardi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The right strategy is needed to be able to follow business developments and compete, one way is to build brand loyalty. The type of research that used by researchers is quantitative research with the analysis technique used is path analysis. The result of this study is that Brand Awareness and Brand Image affect Brand Trust, while Word of Mouth does not affect Brand Trust. Brand Awareness and Word of Mouth affect Brand Loyalty. While Brand Image and Brand Trust have no effect on Brand Loyalty. Brand Awareness and Brand Image affect Brand Loyalty through Brand Trust. Word of Mouth has no effect on Brand Loyalty through Brand Trust.